2010
DOI: 10.1007/s00442-010-1747-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic disturbance and the risk of flea-borne disease transmission

Abstract: Anthropogenic disturbance may lead to the spread of vector-borne diseases through effects on pathogens, vectors, and hosts. Identifying the type and extent of vector response to habitat change will enable better and more accurate management strategies for anthropogenic disease spread. We compiled and analyzed data from published empirical studies to test for patterns among flea and small mammal diversity, abundance, several measures of flea infestation, and host specificity in 70 small mammal communities of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 57 publications
3
38
2
Order By: Relevance
“…However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014). Here, in contrast to other studies on fleas and flea-borne disease (Thamm et al, 2009;Friggens and Beier, 2010), we find no substantial support for a general effect of either disturbance or host diversity on frequency or levels of flea parasitism. Of course, disease risk may still increase via changes in host abundance (Keesing et al, 2006;Young et al, 2014) or competence of hosts or flea species for carrying and transmitting the disease (Johnson et al, 2013), but there was no evidence for a systematic effect of host diversity or anthropogenic disturbance on intensity or prevalence of vectors on hosts in this system.…”
Section: Across Populationscontrasting
confidence: 56%
See 1 more Smart Citation
“…However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014). Here, in contrast to other studies on fleas and flea-borne disease (Thamm et al, 2009;Friggens and Beier, 2010), we find no substantial support for a general effect of either disturbance or host diversity on frequency or levels of flea parasitism. Of course, disease risk may still increase via changes in host abundance (Keesing et al, 2006;Young et al, 2014) or competence of hosts or flea species for carrying and transmitting the disease (Johnson et al, 2013), but there was no evidence for a systematic effect of host diversity or anthropogenic disturbance on intensity or prevalence of vectors on hosts in this system.…”
Section: Across Populationscontrasting
confidence: 56%
“…This is of particular interest in light of increasing interest in the effects of human disturbance and host diversity on levels of parasitism and particularly on disease transmission. Multiple studies have argued that high host diversity and low levels of anthropogenic disturbance tend to lead to lower intensities and prevalence of parasitism and disease in a wide range of systems (Keesing et al, 2010;Haas et al, 2011;Lacroix et al, 2014;Venesky et al, 2014), with vector-borne diseases in rodents being one important study system (LoGiudice et al, 2003;Friggens and Beier, 2010). However, other studies have failed to find a causal relationship (Giraudoux et al, 2013;Oda et al, 2014), or they have found idiosyncratic relationships across hosts, parasites, and environmental conditions (Froeschke et al, 2013;Salkeld et al, 2013;Young et al, 2013a;Kedem et al, 2014).…”
Section: Across Populationsmentioning
confidence: 96%
“…As discussed above, different mechanisms may apply to wildlife versus artificially housed companion animals, for which the relationship to the environment may differ. The considerable and unprecedented land use and climate changes and also the presumably changing abundances of wild and domestic animals which we have to expect during the next decades will most probably alter host-parasite associations for both wildlife and companion animals, with possible consequences for biodiversity and human health (Daszak et al 2001;Friggens and Beier 2010;Lafferty 2009), suggesting a need for more epidemiological studies.…”
Section: Discussionmentioning
confidence: 98%
“…This might have an effective repercussion on the human health risk in zoonotic diseases. Moreover, man-made disturbances such as movements of livestock by nomads and intensive animal breeding practices and/or natural disasters could create conditions conducive to enhanced transmission of flea-borne microbial and parasitic infections (Friggens and Beier 2010;Fakoorziba et al 2011).…”
Section: Discussionmentioning
confidence: 99%